The Impact of COVID-19 Vaccines on the Development of Acute Complications in Type 1 and 2 Diabetes Patients: A Cross-Sectional Study in the Eastern Province of Saudi Arabia - Alhawaj SA; Almuhanna AS; Alabbad FS; Almomattin HH; Alsultan RS; Shaiban ZA; Vatte C; Cyrus C (International Journal of General Medicine, 2023)
Sharook A Alhawaj,1 Alia Saeed Almuhanna,1 Fatimah Saeed Alabbad,1 Hadeel Hisham Almomattin,1 Ragad S Alsultan,1 Zahra Abdulla Shaiban,1 Chittibabu Vatte,2 Cyril Cyrus2 1College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2College of medicine, Department of Biochemistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Sharook A Alhawaj, College of Medicine, Imam Abdulrahman bin Faisal university, Dammam, 34212, Saudi Arabia, Tel +966595292920, Email shroog7676@gmail.comBackground: COVID‐19 vaccines were developed to control the pandemic spread as they have been proven to be efficient and safe. However, the likelihood of such postvaccination effects as poor glycemic control and adverse events has been noted in several studies.Objective: To determine the effect of COVID-19 vaccines on the glycemic control and the development of hyperglycemic emergencies among type 1 and 2 diabetes patients.Methods: A cross-sectional study was conducted on 409 participants aged 18 years and above with type 1 or 2 diabetes who had received at least a single dose of COVID-19 vaccine.Results: Among the 409 diabetes patients, a majority reported general mild postvaccination symptoms regardless of diabetes duration or type. After vaccination, severe diabetic emergencies were mostly reported in long-standing diabetes patients. Diabetes-related complications and emergencies were more profound among those who had received the Pfizer vaccine. Nonetheless, occurrence of adverse events could possibly be due to various factors, including the duration of diabetes and COVID-19 infection status.Conclusion: COVID-19 vaccinations have the potential to influence diabetic patients in regard to acute glycemic complications. However, vaccine efficiency and benefits are superior to the side effects of COVID-19 vaccines, as these adverse events only affect a small number of individuals. A need for postvaccination monitoring of diabetes patients is suggested.Keywords: diabetes, vaccine, COVID-19, hyperglycemic emergencies, diabetes complications